IMPLEMENTASI PERNYATAAN STANDAR AKUNTANSI KEUANGAN (PSAK) NO. 16 TENTANG ASET TETAP PADA CV. HATI MULIYA DI KAB. GOWA - Rianthy, Gina Anggi; HS, Sri Wahyuni (Patria Artha Journal of Accounting dan Financial Reporting, 2025)
This research aims to find out the suitability of the fixed assets at CV. Hati Muliya with Statement of Financial Accounting Standards (PSAK) No. 16. This research uses a qualitative descriptive analysis technique, which aims to determine the actual situation that occurs in the management of fixed assets at CV. Hati Muliya by collecting data, doing data reduction, concluding and providing suggestions. The results of this research indicate that generally the management of fixed assets CV. Hati Muliya was in accordance with PSAK No. 16 whether it is regarding the classification of fixed assets, recognition of fixed assets, measurement of fixed assets, depreciation of fixed assets, derecognition of fixed assets, presentation and disclosure of fixed assets.